Effectiveness of a hybrid emergency room system in the management of acute ischemic stroke: a single-center experience - Kashiura, Masahiro; Nakajima, Chisato; Kishihara, Yuki; Tominaga, Keiichiro; Tamura, Hiroyuki; Yasuda, Hideto; Ikota, Masashi; Yamada, Kenji; Yoshino, Yoshikazu; Moriya, Takashi (Frontiers in Medicine, 2024)
Introduction: Hybrid emergency room systems (HERSs) have shown promise for the management of severe trauma by reducing mortality. However, the effectiveness of HERSs in the treatment of acute ischemic stroke (AIS) remains unclear. This study aimed to evaluate the impact of HERSs on treatment duration and neurological outcomes in patients with AIS undergoing endovascular therapy. Materials and methods: This single-center retrospective study included 83 patients with AIS who were directly transported to our emergency department and underwent endovascular treatment between June 2017 and December 2023. Patients were divided into the HERS and conventional groups based on the utilization of HERSs. The primary outcome was the proportion of patients achieving a favorable neurological outcome (modified Rankin Scale score 0–2) at 30 days. The secondary outcomes included door-to-puncture and door-to-recanalization times. Univariate analysis was performed using the Mann–Whitney U test for continuous variables and the chi-squared test or Fisher's exact test for categorical variables, as appropriate. Results: Of the 83 eligible patients, 50 (60.2%) were assigned to the HERS group and 33 (39.8%) to the conventional group. The median door-to-puncture time was significantly shorter in the HERS group than in the conventional group (99.5 vs. 131 min; p = 0.001). Similarly, the median door-to-recanalization time was significantly shorter in the HERS group (162.5 vs. 201.5 minutes, p = 0.018). Favorable neurological outcomes were achieved in 16/50 (32.0%) patients in the HERS group and 6/33 (18.2%) in the conventional group. The HERS and conventional groups showed no significant difference in the proportion of patients achieving favorable neurological outcomes (p = 0.21). Conclusions: Implementation of the HERS significantly reduced the door-to-puncture and door-to-recanalization times in patients with AIS undergoing endovascular therapy. Despite these reductions in treatment duration, no significant improvement in neurological outcomes was observed. Further research is required to optimize patient selection and treatment strategies to maximize the benefits of the HERS in AIS management.